DEVELOPING MATHEMATICS LEARNING MEDIA WITH MACROMEDIA FLASH 8 APPLICATION ON THREE DIMENSIONS GEOMETRY - Dhamar Widya Safitri; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Macromedia Flash 8 is still something new in the process of learning mathematics. Even though one of these computer applications can create exciting media for the student, the student will experience different learning styles using a computer to learn. This research aims to design, develop, and find out the qualitative categories and the feasibility of learning media of mathematics based Macromedia Flash 8 on Three Dimensions for 10th Student of Senior High School. The research uses the development method of Research and Development. The development stages are Analysis, Design, Development, Implementation, and Evaluation (ADDIE). This research subject is the matter expert, the media expert, 10th students of Senior High School of Muhammadiyah (SMA Muhammadiyah) 5 Yogyakarta, and 10th students of Senior High School of Muhammadiyah 6 Yogyakarta. This study used the instrument of questionary. The data analysis technique was conducted quantitatively to test the advisability of developed learning media. The research results showed the advisability of learning media, 76.33 from the subject aspect, and 111.33 from the media aspect. The student’s response has an average of 65.20 on a limited class trial and 64.49 on a significant class trial. For the learning media developed, the average score of the final assessment is 317.35, with the category of Excellent and Feasible for use as learning media for the Subject of Three Dimensions for 10th student of Senior High School.